"Form and Use" and Environments for an Open Society: MIT, ca. 1969. Issue 1 (2nd January 2019) - Kauffman, Jordan
Abstract: "Form and Use in Architecture" was constructed and mounted at MIT's Hayden Gallery in 1969. Designed and assembled by students with guidance from Stanford Anderson, then professor at MIT, it was a means to test Anderson's theories of design. The exhibition opposed modernist faith in the predictability of forms' effects. It instead investigated notions of environments, which accounted for interplay between form and person, and understood that how individuals might use those forms was unpredictable. In its design, it prompted multiple readings and encouraged user feedback to inspire attentive, critical participation as a means of testing how design could encourage an open society.